1984
DOI: 10.1029/rg022i001p00073
|View full text |Cite
|
Sign up to set email alerts
|

Planetary energy balance for tidal dissipation

Abstract: Dissipation of tidal energy is expressed here as an integral on the surface of a sphere that encloses the mass of the planet. When developed in constituent form, this surface integral depends linearly on the secondary potential that arises from the tidal disturbance; it can therefore be expressed as the sum of one part due to the body tide and another due to the fluid tides. The body tide part depends only on the anelastic response of the solid earth to the primary potential. The fluid tide part depends mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 16 publications
4
43
0
Order By: Relevance
“…There will thus be an adjustment to both the in-phase and out-of-phase components. This estimate of D sin y for the ocean implies (Platzman 1984;Cartwright & Ray 1991) an oceanic tidal dissipation of 2.421t0.015 TW. The tracking coef®cients (eq.…”
Section: Corrected Oceanic Coef®cientsmentioning
confidence: 82%
See 2 more Smart Citations
“…There will thus be an adjustment to both the in-phase and out-of-phase components. This estimate of D sin y for the ocean implies (Platzman 1984;Cartwright & Ray 1991) an oceanic tidal dissipation of 2.421t0.015 TW. The tracking coef®cients (eq.…”
Section: Corrected Oceanic Coef®cientsmentioning
confidence: 82%
“…The anelasticity that induces the lag e in the Earth's body tide implies a certain loss of tidal energy. Platzman (1984) has shown that the energy dissipation rate in given by P~101:4 TW|k 2 sin e ,…”
Section: Body Tide Energy Dissipationmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 As is well known, the dominant tide in •, responsible for about 70% of the total acceleration, is M2. The next largest tide is S2, but its oceanic effect is partly canceled by the S2 atmospheric tide, which tends to accelerate the Earth's rotation rate by roughly +55" cy -2 (based on spherical harmonic coefficients listed in Haurwitz and Cowley [1973]; see also Platzman [1984] and Cartwright and Ray [1991]; Volland [ 1990] gives an estimate of +80" cy -2 but without the factor (1 + k[).). The totals listed in Table 2 are misleadingly close, a coincidence of favorable cancellations.…”
Section: Secular Braking Of Earth's Rotationmentioning
confidence: 99%
“…The combined effect of the torques exerted by the tiny Martian moons, Phobos and Deimos, is much less than the torque exerted on Mars by the Sun . The torque applied to the Earth by the Moon decelerates the Earth's rotation due to tidal friction in the oceans and, to a minor extent, in the solid Earth (Platzman, 1984;Zharkov et al, 1996). In turn, the Moon is accelerated in its orbit and recedes from the Earth at a rate of a few centimeters per year.…”
Section: Rotation and Tidesmentioning
confidence: 97%